PENGARUH KINERJA KEUANGAN DAN STRUKTUR KEPEMILIKAN TERHADAP RETURN SAHAM - Lilyani, Anggita Ika; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2018)
This research is aimed to examine the influence of financial performance and ownership structure to the stock return. Financial performance is measured by using current ratio, return on assets, debt to equity ratio, and total asset turn over whereas ownership structure is measured by using managerial ownership and institutional ownership. This research is a quantitative research type. The samples have been obtained by using purposive sampling method in which the selection is based on the predetermined criteria. Based on the purposive sampling method, 117 samples have been selected from 39 manufacturing companies which are listed in Indonesia Stock Exchange in 2014-2016 periods. The analysis method has been performed by using multiple linear regressions analysis and 21st version of SPSS program. The result of the research shows that current ratio gives negative influence to the stock returns. Meanwhile, debt to equity ratio, total assets turn over, managerial ownership, and institutional ownership do not give any influence to the stock return.Keywords: Financial Performance, Ownership Structure, Stock Return